Efektivitas Kelompok Kecil (KK) Sebagai Upaya Pembinaan Kerohanian Jemaat Di Gereja JKI Keluarga Kerajaan - Kartika Dewi Kristanti; Chandra Wahyuni Irawati (CV. Multi Kreasi Media, 2024)
Obstacles to the spiritual growth of congregations are often found in many churches. One alternative used to solve this problem is discipleship. Discipleship helps believers to become disciples who have mature faith through community. JKI Royal Family Church is a church that carries out discipleship in a small group called My Team based on the Great Commission written in Matthew 28:19-20. Through small groups, it is hoped that the congregation can grow together spiritually. This research aims to see the effectiveness of small groups as an effort to develop the spirituality of the congregation at the JKI Royal Family Church. The research method used is descriptive qualitative by collecting data through related books, interview scripts and observation results. The data obtained shows the existence of small groups which apparently contribute to the spiritual growth of the congregation. This growth can be seen from the development of the quality of loyalty in participating in worship, changes in character for the better, and more responsibility. Through the results of research conducted in My Team, it can be concluded that small groups can increase the spiritual effectiveness of the congregation.